Development of probiotic fermented smoothie made from "Loka Pere" endemic banana of West Sulawesi - Alwi, Achmad Nur Syawal; Trinoviyani, Trinoviyani; Sudirman, Sudirman (Anjoro: International Journal of Agriculture and Business, 2025)
Functional food products play a crucial role in maintaining human health. One such functional food product that benefits digestive health is probiotic products. Banana "Loka Pere" can be the primary raw material for probiotic products. The monosaccharide and fiber content in the banana "Loka Pere" can serve as substrates for probiotic bacteria. A probiotic fermented smoothie made from banana "Loka Pere" is one such example of a probiotic product. Smoothies were chosen for their superior fiber composition, which remains intact due to the absence of fruit fiber filtration. This study examines and analyzes the growth ability of probiotics through the fermentation process in smoothies made from "Loka Pere" bananas, focusing on the parameters of pH, total acid, and the number of probiotic bacteria. The variables used included variations in probiotic powder (Lacto B and L-Bio) and variations in fermentation time (0 hours, 24 hours, and 48 hours) with three replications. The analysis results showed significant differences in pH, total acid, and probiotic count. The results showed that the use of L-Bio probiotic powder and 48 hours of fermentation time provided the best results, with a pH value of 3.81, a total acid content of 0.69%, and several probiotic bacteria at a log of 7.65 CFU.mL–1.